P746 Living with ulcerative colitis in Germany: quantifying the socioeconomic impact of moderate to severe ulcerative colitis. (25th January 2019) - Dignass, A; Waller, J; Cappelleri, J C; Salese, L; Kisser, A; Dietz, L; DiBonaventura, M; Wood, R; Bargo, D
Abstract: Background: Ulcerative colitis (UC) often manifests in adults at a young age. Disease morbidity results in high societal costs due to the impairment on patients' ability to work. Previous European studies have estimated the cost of UC caused by work loss, but results varied greatly due to varying population characteristics and small sample sizes. Treatment options for inducing and maintaining clinical remission in moderate to severe UC include biologic therapies, and it is not known whether these have a beneficial effect on work impairment and/or societal cost due to UC. We present data from the Living with UC Study in Germany, comparing sick leave and benefits between patients with moderate to severe UC initiated on biologic therapy and general population matched controls. Methods: A retrospective, longitudinal cohort design with comparator group was employed utilising de-identified German statuary health insurance (SHI) claims data within the Health Risk Institute (HRI) database. Adult patients (18+ years) with UC (ICD-10 K51) but without Crohn's disease (ICD-10 K50) were indexed from Jan 2013 to December 2015 on biologic therapy initiation (adalimumab, golimumab, infliximab, vedolizumab). Patients had to be continuously insured by SHI and have no record of biologic therapy in the prior 12 months. UC patients (cases) were matched 1:1 with respect to age, sex and comorbidities to controls from the HRI database without inflammatory bowel disease via a propensity score. The total number of sick leave days in the 24 months following indexing was calculated per-patient. Patients were classified as no leave, short-term leave (<6 weeks – employer pays wages) or long-term leave (≥6 weeks – sick benefits triggered). The amount paid in sick benefits (€) was also calculated. Descriptive analyses were reported. Results: In total, 304 eligible cases were identified (mean age 42.9, 56.3% male). Data on sick leave and benefits for all cases and controls are presented in Table 1, with UC patients experiencing a significantly higher burden in terms of sick leave and benefits. Conclusions: Long-term sick leave among patients with moderate to severe UC was higher vs. the matched general population. These data highlight a significant indirect cost burden associated with moderate to severe UC in spite of biologic therapy. This is further emphasised by the significantly higher degree of long-term sick leave in patients with UC vs. the general population, which results in a greater burden to the German healthcare system due to the significant amount of sick benefits.